Challenges in maintaining the world heritage site status: Georgetown and Malacca / Yasmin Nur Amirah Yaman - Yaman, Yasmin Nur Amirah (Faculty of Architecture, Planning and Surveying, 2015)
Heritage building has it owns architectural, aesthetic, and historical background where it gives us a sense of wonder and attract us to know more about their culture and knowledge. Most of the heritage buildings maintenance is influenced by related problem where it affects the overall building condition and performance. As a result, the numbers of these buildings are suffering from defect problem because it has been neglected and without proper maintenance. The aim of this research study is to study the challenges in maintaining World Heritage Site status in Georgetown and Malacca. The objectives of having this research is to study the criteria for the listing of World Heritage Site, to investigate the challenges faced in Georgetown and Malacca in sustaining of the World Heritage Status recognition and lastly is to recommend the measures to sustain the World Heritage Site status in Georgetown and Malacca. This study involves comprehensive literature reviews in order to gather the information of the World Heritage Site and followed by the structured interview methods as the main tools to obtain the data. The findings shows that there are five (5) challenges that Georgetown and Malacca faced in maintaining the World Heritage Site such as the conservation plan, lack of skilled workers and responsibility challenge of contractor, choice in material, conservation guidelines for conservation works and financial factor. Based on the respondents from the structured interview, they also had recommended a few solutions on how to solve the problem.